2020
DOI: 10.1021/acs.jced.9b00479
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibrium for the Ternary Systems Water + 1-Butanol + 1-Hexanol or 1-Octanol at 303.15, 313.15, and 323.15 K

Abstract: Liquid–liquid equilibrium data (LLE) of ternary systems {water + 1-butanol + 1-hexanol} and {water + 1-butanol + 1-octanol} were investigated at 303.15, 313.15, and 323.15 K at 101.3 kPa. The distribution coefficient (D) and selectivity factor (S) were calculated from experimental LLE data. Meanwhile, the effect of temperature on the two-phase zone of the two systems was discussed. The nonrandom two liquid and universal quasi-chemical activity coefficient models were used to regress experimental data sets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The specific information about uncertainty is provided in the Supporting Information. Generally, the UNIQUAC model and NRTL model are used to regress the LLE data to obtain the binary interaction parameters. After comparison, it was found that the UNIQUAC model had higher accuracy of regression, so in this article, the UNIQUAC model was used to regress the LLE data to acquire the binary interaction parameters. The activity coefficient in the UNIQUAC model is expressed as follows θ i and φ i represent the volume fraction and surface area fraction, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The specific information about uncertainty is provided in the Supporting Information. Generally, the UNIQUAC model and NRTL model are used to regress the LLE data to obtain the binary interaction parameters. After comparison, it was found that the UNIQUAC model had higher accuracy of regression, so in this article, the UNIQUAC model was used to regress the LLE data to acquire the binary interaction parameters. The activity coefficient in the UNIQUAC model is expressed as follows θ i and φ i represent the volume fraction and surface area fraction, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Some similar systems have been studied. The liquid–liquid equilibrium (LLE) for the system water + ethanol + hexanol + decane, water + ethanol + octanol, water + n -butanol + hexanol, water + n -butanol + octanol, water+1-butanol+2-butanol, and n -amyl alcohol + water + acetic acid was studied at different temperatures. Non-random two-liquid (NRTL) and UNIQUAC models were used to correlate the LLE data.…”
Section: Introductionmentioning
confidence: 99%